Assessing statistical literacy in medical students and doctors: a single-centre, cross-sectional survey in South Korea - Un-Na Kim; Jae-Joon Yim; Sun Young Lee; Soyun Kim; Young Kyung Do; Soela Kim; Yukyung Shin; Hyeontaek Hwang; Youngsuk Kwon (BMJ Open)
Objective Healthcare professionals must possess statistical literacy to provide evidence-based care and engage patients in decision-making. However, there have been concerns about healthcare professionals' inadequate understanding of health statistics. As an initial step in addressing the issue, we assessed the statistical literacy of medical students and doctors in South Korea by evaluating their comprehension of four statistical concepts: (a) single-event probability, (b) relative risk reduction, (c) positive predictive value and (d) 5-year survival rate.Design Cross-sectional survey study.Setting The survey was conducted from October 2018 to January 2019 in one medical school and its affiliated teaching hospital in Seoul, South Korea.Participants 303 medical students from all six grades and 291 doctors from various specialties.Primary and secondary outcome measures The primary outcome measure was the correct answer rate for each question. The secondary outcome measure was the mean number of correct answers across the four statistical literacy questions, calculated for each individual.Results The correct answer rates for basic numeracy questions were close to 100%. Regarding statistical literacy, 95.5% and 83.2% of the participants accurately understood single-event probability and relative risk reduction, respectively. However, only 49.3% and 49.2% of the participants accurately understood the positive predictive value and 5-year survival rate, respectively. The correct answer rates for the question about the 5-year survival rate differed significantly between students (40.9%) and doctors (57.7%) (p<0.001). There were no statistically significant differences in the correct answer rates for other questions, regardless of the student’s grade level or the doctor’s specialty.Conclusions Medical students and doctors have weaker statistical literacy than their basic numeracy. Therefore, it is essential to implement medical education and professional development programmes that focus on improving their statistical literacy. These programmes should specifically address measures of medical test accuracy and the distinction between a 5-year survival rate and mortality.